Dallas buyers club [videorecording (DVD)] - Vallée, Jean-Marc; McConaughey, Matthew, 1969-; Leto, Jared, 1971-; Garner, Jennifer, 1972-; O'Hare, Denis, 1962-; Zahn, Steve, 1968-; O'Neill, Michael (Actor); Roberts, Dallas; Dunne, Griffin; Rankin, Kevin, 1976-; Duplantier, Donna
Texas cowboy Ron Woodroof's free-wheeling life was overturned in 1985 when he was diagnosed as HIV-positive. Shunned and ostracized by many old friends and bereft of government-approved medicines, he decided to take matters in his own hands, tracking down alternative treatments from all over the world by means both legal and illegal. Bypassing the establishment, he joined forces with an unlikely band of renegades and outcasts and established a hugely successful "buyers' club."